A traíra Hoplias aff. malabaricus (Bloch, 1794) na planície de inundação do alto rio Paraná : influência sobre as assembléias de peixes e aspectos da auto-ecologia. - Petry, Ana Cristina (2005)
Cap.1: This study tested experimentally the hypothesis that traíra Hoplias aff. malabaricus is a keystone predator in isolated lagoons of the upper Paraná River floodplain. The experiment was conducted from April to October 2002, through an initial manipulation of traíra density (levels of treatment: addition, removal and reference). Treatment effects were evaluated on descriptors of fish assemblage structure (species richness, abundance, equitability and biomass), through repeated measures analysis of variance, in two habitat categories (open and macrophyte-dominated areas). In spite of being recorded in all assemblages and depended on habitat category, reductions in species richness were significantly more pronounced in lagoons where H. aff. malabaricus was removed. In these lagoons, the number of individuals was also significantly lower than in those where the piscivore was added or maintained in natural densities. Equitability showed opposite tendencies. Analysis of relative abundance by size-classes revealed a sharp reduction in the number of small-sized individuals (< 3cm), contributing to the absence of pronounced alterations in biomass. These evidences supported our hypothesis and demonstrated that the understanding of mechanisms by which predators affect the persistence of prey species constitutes a challenge for future researches, especially in tropical ecosystems.